Learners' attitudes towards error-related issues in EFL writing classes : - Dương, Thị Diễm Phúc (Can Tho University, 2009)
This study aimed to investigate EFL learners' attitudes towards written errors, towards error correction, and towards teacher correction, peer correction and self-correction with teachers' help; and find out what type of correction learners perceived as the most favorable and efficient type to improve their writing accuracy and writing performance.